Recent advances of antioxidant low-dimensional carbon materials for biomedical applications - Tang, Nan; Ding, Zhen; Zhang, Jin; Cai, Yanting; Bao, Xingfu (Frontiers in Bioengineering and Biotechnology, 2023)
As the primary cause of many tissue damage and diseases, reactive oxygen species (ROS) are well known to be extremely harmful to a variety of biological components in cells including lipids, proteins and DNA. Numerous antioxidative nanomaterials have been artificially designed and rationally synthesized to protect cells from the oxidative damage caused by ROS. Recent studies demonstrate that low dimensional carbon antioxidative nanomaterials have received a lot of attention owing to their tiny nanoscales and unique physicochemical property. As a result, a brief overview of recent advancements in antioxidant low-dimensional carbon materials is provided. Typically, carbon nanomaterials are classified according to their nanostructure dimensions, which are zero-dimension, one-dimension, and two-dimension. Last but not least, the challenges and perspectives of these high-performance low-dimensional materials in biomedical fields and further clinical usages are discussed as well.